선천성 무질증 환자에서 복막이용 복강경 질재건술(Davydov techique) 47예의 임상적 연구 - 박기현; Ki Hyun Park; 박주현; Joo Hyun Park; 양효인; Hyo In Yang; 최보람; Bo Ram Choi; 백정혜; Jeong Hye Baek; 홍연; Yeon Hong; et al. (Obstetrics & gynecology science, 2012)
목적 본연구는 선천성 무질증 환자에서 복강경하에서 복막을 이용한 질재건수술 환자에서 수술 후 추적기간 동안 재건된 질의 해부학적 및 성기능을 연구한다. 연구방법 2005년과 2011년 사이에 연세의료원과 안양샘병원 산부인과에 내원한 47명의 무질증 환자(로키탄스키증후군)에서 복강경하에서 복막을 이용한 질재건술(laparoscopic Davydov technique)을 시행하였으며, 수술 후 3-12개월의 추적기간 동안 재건된 질의 길이, 넓이, 편평상피세포 전환과 세포성숙도를 알기위해 Schiller test을 시행하였다. 이 중 성교활동이 활발한 25명의 환자에서 성적만족도를 알기위해, 비슷한 년령의 일반대조군 기혼여성 15명과 성만족도(Female Sexual Function Index)를 비교조사하였다. 수술전 환자는 염색체검사, 호르몬검사, 및 MRI을 시행하였으며, 기타 비뇨기계 및 골격계기형유무를 알기위해 신우조영술 및 기타 방사선촬영을 시행하였다. 결과 평균수술 시간은 117 ± 35.3분이었으며, 수술 중 합병증으로서 2예에서 직장손상, 1예에서 방광손상이 있었으며, 그 이후 3-12개월 추적기간 동안, 경등도의 탈장 및 질육아조직미란이 각각 1예씩 관찰되었으며, 그 외 직장질루 또는 방광질루 등은 관찰되지 않았다. 추적환자의 평균 질길이는 8.3 ± 1.1 cm이었으며, 질의 넓이는 전환자에서 최소한 두 손가락(3 cm)이 통과되었으며, 성만족도는 일반 대조군과 차이가 없었다. 결론 복강경 Davydov 수술은 매우 안전하고, 합병증이 적으며, 해부학적 및 기능적으로도 우수한 결과를 얻었다. 이 수술법은 복강경하에서 최소침습시술을 함으로써 신체외부에도 보기 흉한 흉터를 남기지 않으며, 복막을 이용함으로써 자연적인 골반축을 유지할 수 있으며, 또한 자연질상피세포로의 전환이 용이하게 일어나 질건조나 위축이 적어 성적 만족도도 우수하였다. 또한 특별한 수술기구가 필요하지 않았으며, 부인과 의사가 단독으로 시행할 수 있는 좋은 수술법으로 생각된다. Objective To evaluate the technical feasibility and anatomical and functional outcomes of laparoscopic Davydov technique (transvestibular vaginoplasty with pelvic peritoneum) for the patients with Mayer-Rokitansky-Kuster-Hauser (MRKH) syndrome. Methods This study was a retrospective review of prospectively collected data of 47 women with MRKH syndrome between 2005 and 2011. Clinical examination, pelvic ultrasound, intravenous urography and/or renal ultrasound, laparoscopy, karyotyping, orthopedics and ears, nose, and throat examination, magnetic resonance imaging was performed and 47 patients with MRKH syndrome underwent surgery with the procedure. Their clinical, surgical, and follow-up data were recorded and the functional outcome was assessed by a brief and valid self-report questionnaire evaluating female sexual life (Female Sexual Function Index, FSFI). A control group was recruited to compare the results. Results The mean operative time was 117.2 ± 35.3 minutes. Two intra-operative rectal and one bladder injury were repaired without sequels. One patients had vault granulation at the neovagina, which healed after electric cautery and one patient had mild enterocele. The mean length of the neovagina was 8.3 ± 1.1 cm (range, 6 to 11 cm) without any shrinkage at the follow-up of 18.9 months (range, 6 to 53 months) after operation. The neovaginal introitus admitted two fingers in width in all patients. There was no statistical difference in the total FSFI between the case and control groups. Conclusion Laparoscopic Davydov is a safe, effective treatment of MRKH syndrome with minimal invasion and a relatively low complication rate. The procedure has satisfactory anatomical and functional results. This technique offers advantages such as: short operating time and hospital stay, no particular instrumentation required and no external scars. Sexuality approaches so-called ``normal sexuality.``